2008
DOI: 10.1007/s11605-008-0548-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Three Types of Alimentary Reconstruction After Total Gastrectomy

Abstract: Orr-type Roux-en-Y reconstruction method can avoid reflux esophagitis, and the procedure is simpler than the other two methods. Therefore, Orr-type Roux-en-Y reconstruction can be recommended as an adoptable method of digestive reconstruction after total gastrectomy for gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…For those patients with whole gastric cancer, proximal gastric cancer and diffuse gastric cancer, total gastrectomy remains the main curative therapy, particularly for malignant tumors occurring at the gastric-esophageal junction. The majority of clinicians now recommend total gastrectomy for these patients to reduce gastric reflux (12,13). Previous findings indicated that patients requiring total gastrectomy were usually diagnosed with late stage cancer by pathological observations (4), necessitating post-operative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…For those patients with whole gastric cancer, proximal gastric cancer and diffuse gastric cancer, total gastrectomy remains the main curative therapy, particularly for malignant tumors occurring at the gastric-esophageal junction. The majority of clinicians now recommend total gastrectomy for these patients to reduce gastric reflux (12,13). Previous findings indicated that patients requiring total gastrectomy were usually diagnosed with late stage cancer by pathological observations (4), necessitating post-operative chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…They have been designed to improve patients' lives post gastrectomy and to attempt to maintain disease free progression, improving overall survival. Hong bo Wei et al reported that over seventy (70) surgical procedures currently exist for the management of gastric cancer after total or subtotal gastrectomy [ 3 ]. However, the optimal digestive reconstructive method remains a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Most methods of forming an esophageal-intestinal anastomosis are aimed at increasing its reliability and do not provide for the creation of an anti-reflux mechanism that provides physiological, batch evacuation of food [9,10]. Prevention of functional impairment after gastrectomy is estimated as an exceptional parameter for improving the quality of life of patients who have undergone an already complicated surgical procedure [8,11].…”
Section: Introductionmentioning
confidence: 99%